LITERASI KEUANGAN UNTUK SISWA: EFEKTIVITAS BUKU CERITA ANAK BERGAMBAR DALAM EDUKASI FINANSIAL DI SEKOLAH DASAR - Wibowo, Wahyu (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
Financial literacy is an essential skill that needs to be taught early on to form healthy financial habits in children. However, the level of financial literacy of children in Indonesia is still low due to curriculum limitations and the lack of interesting learning resources. This study aims to analyze the effectiveness of illustrated children's storybooks as a medium for financial education for children. Using a qualitative approach with a literature study method, this study examines various literature related to children's financial literacy, story-based learning strategies, and factors that influence children's understanding of financial concepts. The results of the study indicate that illustrated storybooks can improve children's financial understanding in an interactive and fun way, especially if accompanied by the involvement of parents and educators. The main factors that influence its success include the quality of content, illustrations, and the relevance of the story to children's lives. These findings confirm that the development of interesting and educational financial storybooks can be a strategic solution in building financial awareness from an early age, as well as supporting financial literacy policies at the elementary school level.